EARLY CHILDHOOD SEX EDUCATION WITH AL ISLAM MUHAMMADIYAH VALUES INSIGHTS (A CASE STUDY IN BUSTANUL ATHFAL BANGUNSARI PONOROGO) - Sidik Nuryanto (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
This research was entitled Early Childhood Sex Education with Al Islam Muhammadiyah Values Insights (A Case Study in Bustanul Athfal Bangunsari Ponorogo). This research used a case study method with data collection observations, interviews, and documentation. Data validity was conducted by examining the degree of trust, transfer, dependency and certainty. Data analysis with interactive models consisted of data reduction, data presentation, and conclusion drawing. The results of the study included cognitive relating to the transfer of knowledge, psychomotor skills provision, and affective relating to the norms of sex education and the values of Al Islam Muhammadiyah. The supporters and inhibitors came from teachers, parents, and infrastructure.